(untitled) (Anwer Khan Modern Medical College Journal, 2022)
Background : Having the normal life expectancy of thyroid cancer patients, there are great concerns about any impairment in health-related quality of life (HRQOL) during the follow-up period. The aim of this study is to determine the potential predicting factors of health related quality of life (HRQOL) of thyroid cancer patients. Methods : Total 246 thyroid cancer patients in two tertiary level hospitals in Dhaka city were involved in this cross sectional study from 01 July 2018 to 30 June 2019. Data were collected purposively by face-to-face interview with semi-structured questionnaire andchecklist. Data were analyzed by the statistical package for the social science (SPSS) version 23. Results : Study revealed that mean (±SD) age of the respondent was 37.85(±12.20) years (range 14-70 years).Majority 74.4% of respondents was female, married (72%), housewife (61.4%),primary education (69%) and mean (±SD) monthly family income was Tk. 17681(±10602).Approximately 82.9% of patients had papillary cancer and 17.1% had follicular cancer. Of the patients, 91.5% had neck swelling, 41.9% had swollen lymph node, 57.3% had dysphonia and 35.4% had dysphagia.The mean overall HRQOL in thyroid cancer patients was 73.7(±8.39). HRQOL score of students and higher educated persons were better among the respective groups (p <.001).Multivariate regression analysis revealed that education (β=-0.888, p<.05), family income (β=0.05, p<.05) and marital status (β=-0.1.384, p<.05) and clinical condition (β=-0.522, p<.05) were potential predictors of HRQOLof thyroid cancer patients. Conclusion : The overall HRQOL score was considerably good in this study. Family income, marital status, education and clinical condition had emerged as strong predictors in HRQOL of thyroid cancer patients. Proper diagnosis, motivation and attending clinical condition may significantly improve the HRQOL of thyroid cancer patients. AKMMC J 2021; 12(2): 76-81